2015
DOI: 10.1016/j.apsb.2015.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Circadian rhythms in liver metabolism and disease

Abstract: Mounting research evidence demonstrates a significant negative impact of circadian disruption on human health. Shift work, chronic jet lag and sleep disturbances are associated with increased incidence of metabolic syndrome, and consequently result in obesity, type 2 diabetes and dyslipidemia. Here, these associations are reviewed with respect to liver metabolism and disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
88
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(89 citation statements)
references
References 118 publications
1
88
0
Order By: Relevance
“…Many studies have demonstrated the effects of normal circadian action on health and the disruption of circadian rhythm, which can have adverse effects on metabolic function (2,3). Several people work at night or work a rotating shift, employed as police, doctors and nurses and airport services.…”
Section: Aimsmentioning
confidence: 99%
“…Many studies have demonstrated the effects of normal circadian action on health and the disruption of circadian rhythm, which can have adverse effects on metabolic function (2,3). Several people work at night or work a rotating shift, employed as police, doctors and nurses and airport services.…”
Section: Aimsmentioning
confidence: 99%
“…Shift work-induced circadian misalignment is associated with higher rates of metabolic, cardiovascular, and neoplastic disease. Clinical experience suggests time of day can have a marked effect on disease severity (2)(3)(4). Indeed, the majority of the best-selling prescription drugs and World Health Organization essential medicines target molecules that oscillate in mice (1).…”
mentioning
confidence: 99%
“…Clock and Bmal1 form a heterodimer and transactivate through E-Box elements the Per (Period-1 and 2) and Cry genes (Cryptochrome-1 and 2). Per and Cry proteins in turn interact with Clock/Bmal1 and attenuate their own transactivation [5, 8, 17]. In addition to Clock/Bmal1, we and other investigators have demonstrated that DEC transcription factors, differentiated embryo chondrocyte-1 and 2, are strong E-box binding proteins [1820].…”
Section: Introductionmentioning
confidence: 97%